Bleb failure and intraocular pressure rise following Nd: Yag laser capsulotomy - Diagourtas, Andreas (BMC Ophthalmol, 2017)
BACKGROUND: To report the negative effect of Nd: Yag (Neodymium-doped: Yttrium Aluminium Garnet) laser capsulotomy on the intraocular pressure (IOP) and the trabeculectomy bleb integrity, in a small series of eyes, both trabeculectomised and pseudophakic, following the laser application for the management of posterior capsular opacification (PCO). METHODS: This is a retrospective, non-comparative interventional case series study, in which 20 trabeculectomised and pseudophakic eyes from 15 patients, with otherwise well functioning blebs, were presented with uncontrolled IOP, in a variable distance of time following the application of YAG laser capsulotomy. Student paired t-test confirmed a statistically significant difference (P < 0.05) between IOP before Nd: YAG laser capsulotomy (16 mmHg ± 3 mmHg) and the respective one, 2 to 6 months after Nd: Yag capsulotomy (34.5 ± 11 mmHg). RESULTS: All of the cases failed to respond to conservative treatment and were successfully managed with the implantation of Ahmed drainage devices. All patients showed flat filtering bleb and uncontrolled IOP (34.5 ± 11 mmHg), under maximum topical treatment, in a period of 2 to 6 months following Nd: YAG laser caspulotomy. The implantation of Ahmed valve proved to be effective treatment for these patients (IOP < 21 mmHg). CONCLUSIONS: Although Nd: Yag laser capsulotomy is considered a safe surgical procedure and usually is done without second thought, in this series of eyes, it is postulated that it may be responsible for the deregulation of the filtering bleb and subsequent loss of IOP control. We consider that laser capsulotomy should be performed with caution, especially in eyes with previous trabeculectomy. Also close monitoring of the intraocular pressure and assessment of eventual bleb morphology variations in the follow-up period is mandatory. Further studies are needed in order to confirm our findings.